Role of Lysosomal Cathepsins in Post-Myocardial Infarction Remodeling - Chen, MD, Han; Wang, MD, PhD, Jing; Wang, MD, Jian-An; Shi, DSc, Guo-Ping (North American Journal of Medicine and Science, 2011)
Left ventricular remodeling after myocardial infarction (MI) includes extensive cardiac cell death, inflammatory cell infiltration, cell differentiation, and scar formation. Lysosomal proteases cathepsins participate in all these events during post-MI cardiac repair. These cathepsins cleave Bcl-2 interacting protein Bid, and degrade the anti-apoptotic members Bcl-2, Bcl-xL and Mcl-1, thereby triggering a mitochondrial pathway of apoptosis. Cathepsins also contribute to monocyte and macrophage differentiation and migration. Monocytes, macrophages, and neutrophils are recruited to the site of infarction, where they also release lysosomal cathepsins as inflammatory mediators to regulate post-MI inflammatory responses. Cathepsins also regulate fibroblast trans-differentiation and further affect collagen or other matrix protein synthesis during post-MI extracellular matrix remodeling.